Golden Ages, Red Herrings and Post-Keynesian Policing - Understanding the Role of Police Culture in the Police Professionalism Debate - Tom Cockcroft (Nordisk Politiforskning)
This paper seeks to further our understanding of the role played by police culture in debates surrounding police professionalization. It begins with a brief overview of the ‘Golden Age’ of policing which has become the benchmark for public satisfaction against which subsequent eras of British policing are now judged. This is followed by an introduction to the concepts of police professionalism and police culture and an overview of some existing literature that highlights the cultural challenges of police ‘professionalization’. The paper then seeks to position police professionalization agendas as a direct result of social change and the emergence of post-Keynesian policing. This leads into an exploration on how professionalization agendas (in their broadest sense) can be viewed as an attempt to impose, rather than remove, control from practitioners. Finally, the paper develops two related themes. First, that the discretion which is synonymous with the police role makes the imposition of greater occupational control problematic and, second, that being seen to control occupational culture is increasingly viewed as a measure of effective police leadership.